2018
DOI: 10.1038/s41467-018-03200-4
|View full text |Cite
|
Sign up to set email alerts
|

Route to high-energy density polymeric nitrogen t-N via He−N compounds

Abstract: Polymeric nitrogen, stabilized by compressing pure molecular nitrogen, has yet to be recovered to ambient conditions, precluding its application as a high-energy density material. Here we suggest a route for synthesis of a tetragonal polymeric nitrogen, denoted t-N, via He-N compounds at high pressures. Using first-principles calculations with structure searching, we predict a class of nitrides with stoichiometry HeN4 that are energetically stable (relative to a mixture of solid He and N2) above 8.5 GPa. At hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
92
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(99 citation statements)
references
References 54 publications
5
92
0
Order By: Relevance
“…The known compounds consisting of He are either charged molecular species such as helium hydride ion (HeH + ) 19,20 , or the pressure stabilized van der Waals compounds, such as Ne(He) 2 21,22 and He(N 2 ) 11 23 . Interestingly, He was also shown to form HeN 4 in a pressure range from 8.5 to 69 GPa 24 .…”
mentioning
confidence: 97%
“…The known compounds consisting of He are either charged molecular species such as helium hydride ion (HeH + ) 19,20 , or the pressure stabilized van der Waals compounds, such as Ne(He) 2 21,22 and He(N 2 ) 11 23 . Interestingly, He was also shown to form HeN 4 in a pressure range from 8.5 to 69 GPa 24 .…”
mentioning
confidence: 97%
“…The addition of helium can also reduce the pressure at which polymerization of nitrogen may occur. [35]. It has been reported that helium can react with water to form He(H 2 O) 2 at very high pressures (297 GPa) [36].…”
mentioning
confidence: 99%
“…The latest research has identified helium reacting at high P-T conditions with other elements or compounds, such as water [8], sodium and sodium oxide [9], nitrogen [10], and iron [11], but no connections to the deep-Earth helium reservoir have been established. Meanwhile, a theoretical analysis [12] shows that helium tends to react under high pressure with ionic compounds containing an unequal number of cations and anions.…”
mentioning
confidence: 99%